PENELITIAN PENDAHULUAN PENGARUH TEMPERATUR TERHADAP SURVIVAL EMBRIO DAN EBRIOGENESIS IKAN SILAIS TRICOPTERIS LIMPOK - Thamrin Thamrin; Abdul Patah Rasyidi; Mulyadi Mulyadi; Rosyadi Rosyadi (Jurnal Ilmu Lingkungan, 2010)
The experiment and observation of embriogenesis of Silais fish (Criptopteris limpok) wereconducted in Laboratory of Agriculture Faculty, Islamic University of Riau in December 2009.The aim of this study was to investigate the effect of temperature on a number of newly hatchedC. limpok and to describe the embriogenesis. Survival rate of larvae was 5 times higher intreatment (25oC) compared with control (29oC), i.e. 5% in treatment and 1% in control. Thenumber of larvae survival rate was low, but this condition was predicted causeb by low qualityof gamet. Embriogenesis development of eggs need 24 hours of length period of time to hatch,and they have a yolksac during 4 days.